The antecedents and consequences of relationship quality of retail loyalty programmes / Nor Asiah Omar - Omar, Nor Asiah (2008)
Relationship quality has received increasing attention by researchers during the past decade. Research evidence has revealed that relationship quality has an influence on relationship outcomes such as customer loyalty, repurchase intention and word-of-mouth. Based on these reasons, relationship quality has received more overt emphasis by both academicians and practitioners. The data for this research were collected from 400 retail loyalty programme members in Malaysia via drop off and collect survey technique.